Validation of the Mentalization Scale (MentS) in francophone control and clinical samples - Flora Descartes; Vincent Besch; Margaux Bouteloup; Rosetta Nicastro; Eléonore Pham; Eva Rüfenacht; Nader Ali Perroud; Martin Debbané (PLoS ONE, 2025)
Aims The Mentalization Scale (MentS) is a self-report measure for the assessment of mentalizing capacities, consisting of 28 items, yielding a three-factor structure: self-mentalizing, mentalizing others and motivation to mentalize. Its anglophone version has been validated for usage in both research and clinical contexts. The present study explores the psychometric properties of the francophone translation of the MentS, in both control and clinical samples. Method A total of 711 participants were enrolled in this study. The MentS was administered to a community sample (N = 302, 161 females, Mage = 37.1, SDage = 12.3), and to a clinical sample composed of participants diagnosed with borderline personality disorder (BPD), attention deficit hyperactive disorder (ADHD) and co-occurring BPD and ADHD (N = 409, 266 females, Mage = 32.5, SDage = 11.9). Confirmatory factory analysis was used to analyze the fit of the model in our data, followed by reliability and validity analyses. Results Results from confirmatory factor analysis (CFA) revealed a 27-item model to best fit the data for both control and clinical samples. In the control sample, good internal consistency was found for the total scale (α = 0.856, ω = 0.867) as well as for the three subscales MentS-Motivation (α = 0.789, ω = 0.801), MentS-Other (α = 0.792, ω = 0.798) and MentS-Self (α = 0.824, ω = 0.828). Similarly, good internal consistency was found in the clinical sample for the total scale (α = 0.871, ω = 0.879) and subscales (Motivation α = 0.770, ω = 0.783) (Others α = 0.842, ω = 0.847) (Self α = 0.808, ω = 0.815). The MentS demonstrated good temporal stability over a one-year interval, with excellent average-measures ICC for the total scale (ICC = .877, 95% CI [.843,.904], p < .001), and strong reliability for the Motivation (.837), Others (.806), and Self (.837) subscales (all ps < .001). The validity of the scale was confirmed using additional measures showing a coherent pattern of associations in relation to components underlying the construct of mentalization: reflective functioning, childhood trauma, cognitive emotion regulation, overall psychopathology distress and borderline symptomatology. Conclusion & Clinical Implications The MentS can be used for research and clinical purposes in francophone samples. Our results suggest that amongst French speaking samples, a 27-item solution may be most optimal in both clinical and control populations. Evidence shows the scale could be employed across diagnostic entities, and that participants scoring low in self-mentalizing (MentS-Self subscale) may be more likely to report increased manifestations of psychopathology.